If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4s + 4t = 0 Solving 4s + 4t = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-4t' to each side of the equation. 4s + 4t + -4t = 0 + -4t Combine like terms: 4t + -4t = 0 4s + 0 = 0 + -4t 4s = 0 + -4t Remove the zero: 4s = -4t Divide each side by '4'. s = -1t Simplifying s = -1t
| 6x-17=2x+3 | | 8(x-3)=-7(x+2)+47 | | r-1=4+6r | | 32+8x=38+7x | | x*x+7x=11 | | 3x^(1/2)-13x^(1/4)-30=0 | | 0=16t^2+60t+4 | | -3=3(6x)+4x | | X^2x=24 | | 3x^1/2-13x^1/4-30=0 | | 6(n+3)=30 | | 7/3×13/8 | | 2/4y-1=1/4 | | y=16t^2+60t+4 | | b-3a= | | -4x7/-14 | | 7/3×13/8= | | -3(n+5)-5n=-5n-39 | | 1.2p+3.7=34.6 | | 10+p=25 | | 4-10r=56 | | -70-6x=-12x+20 | | 3p+6=24 | | tan(2x)-2tanx=0 | | 4x+4=3x-3.5 | | 28p=28 | | -3+-5+8= | | X-72=7x+88 | | X-6-7=-12+2x | | 5(x+3)-4(x+1)=0 | | x^2+4x+1-x^2+17=0 | | ln(3t)=1.9 |